THE ANALYSIS OF MICROBIC STRUCTURE OF THE ROOT CHANNEL AT PERSONS WITH CHRONIC APIKAL PERIODONTITIS AND PERIODONT INFLAMMATORY DISEASES - Купчак, О.І. (World of Medicine and Biology, 2014)
The purpose of researches consisted in studying of possibility of infection of root channels by periodontal microflora at persons with various degree of expressiveness of inflammatory process in a periodont. Results of studying of contents of the root channel at persons with chronic apiсal periodontitis and a different state of periodont (intact, gum inflammation, a periodontal disease) showed that existence of inflammatory a periodontal disease promote infection of the root channel. And, the more extent of destruction periodont, the is higher activity of periodontal microflora.The study involved three groups of individuals with chronic periodontitis: the first - with intact mucous membrane (or local gingivitis) (10 patients); Second - those with generalized gingivitis (9 people), third -person with periodontitis early. and 1 tbsp. (9 people). All persons with chronic periodontitis was first conducted endodontic treatment. In all the studied intensity decay (CPU ) [7], oral hygiene status by index Greene - Vermylyona [8] and the state of periodontal indices by PMA and PI [9]. Conducted bacteriological sampling material from the root canal, which were plated on medium cultivation of bacteria under aerobic and anaerobic conditions. Identification of isolated strains was carried out on the basis of morphological, cultural and biochemical features in accordance with number of bacteria E. Bergi
Keywords: periodontal disease; chronic apikal periodontitis; microflora of the root channel